2017
DOI: 10.1002/aoc.3946
|View full text |Cite
|
Sign up to set email alerts
|

Supported copper (I) catalyst from fish bone waste: An efficient, green and reusable catalyst for the click reaction toward N‐substituted 1,2,3‐TRIAZOLES

Abstract: An eco-efficient, green, and multi-gram procedure is presented for one-pot multicomponent synthesis of N-substituted 1,2,3-triazoles by using waste fishbone powders supported CuBr (FBPs-CuBr) as catalyst. FBPs-CuBr is found to be an efficient heterogeneous catalyst and a series of 1,2,3-triazoles are obtained in moderate to excellent yields in water under MW irradiation (70-98%). It can be separated conveniently by a simple filtration and reused at least seven consecutive runs with a slight drop in the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…In 2018, Xiong et al offered a new method to organize fishbone powder supported CuBr (FBPs/CuBr) and its utilization as an eco-efficient, stable, and separable catalyst in the MW irradiation assisted production of 1,2,3-triazoles (Scheme 9). 63 The catalyst can be removed easily by filtration and reused in seven successive runs.…”
Section: Applications Of Bone Waste-based Catalysts In Synthetic Orgamentioning
confidence: 99%
“…In 2018, Xiong et al offered a new method to organize fishbone powder supported CuBr (FBPs/CuBr) and its utilization as an eco-efficient, stable, and separable catalyst in the MW irradiation assisted production of 1,2,3-triazoles (Scheme 9). 63 The catalyst can be removed easily by filtration and reused in seven successive runs.…”
Section: Applications Of Bone Waste-based Catalysts In Synthetic Orgamentioning
confidence: 99%
“…Application of microwave irradiation and recyclable alumina-CuI catalyst in the multicomponent synthesis of 1H-1,2,3-triazole derivatives. 234 Recently, a multicomponent method involving propargyl bromide, amines and organic azides has been reported by Xiong et al 235 In this procedure, CuBr was supported on fish bone powder residue generating the catalyst FBPs-CuBr, which was efficient in the preparation of several N-substituted 1H-1,2,3-triazoles and could be reused for seven reaction cycles (Scheme 37). In addition, a scaling up to 40.0 mmol showed that the method has potential for industrial applications.…”
Section: Scheme 25mentioning
confidence: 99%
“…Use of FBPs-CuBr as a recyclable catalyst in the multicomponent synthesis of 1H-1,2,3-triazole derivatives. 235 3.3.7 Multicomponent CuAAC reactions. Multicomponent Reactions provide ideal approaches for synthesizing structurally simple or complex molecules in a few reaction steps and with excellent overall yields.…”
Section: Scheme 25mentioning
confidence: 99%
“…In recent years, low‐cost and green synthesis of supported catalysts from biomass has attracted growing interest . In continuation of our efforts to develop green, highly efficient and practical chemical methods as well as a focus on the application of biomass‐based heterogeneous catalysts in organic reactions, we identified that Schiff base‐functionalized expanded corn starch‐supported CuBr (ECS‐SB‐CuBr) in the presence of TEMPO as a co‐catalyst was an efficient catalyst for promoting the selective aerobic oxidation of HMF into DFF under ambient pressure of dioxygen at 50°C in acetonitrile (Scheme ).…”
Section: Introductionmentioning
confidence: 99%